The role of international financial institutions in macroeconomic crises: improving the architecture of the World Bank and the IMF for managing shocks in developing countries - Kathrin Berensmann; Peter Wolff (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
In their response to the global financial crisis, the international financial institutions (IFIs) have not only increased funds for shock financing, but have also significantly reformed their instruments. Nevertheless, some gaps remain. IFIs should consider the fact that most advanced low-income countries (LICs), which tend to have sound records of macroeconomic performance and are to some degree integrated into international financial markets, will graduate in the foreseeable future. For this group of countries, an International Development Assistance (IDA) blended financing facility with a lower degree of concessionality would be appropriate and would also help IDA to sustain its funding. Similarly, the question arises about whether the lending policy of the International Monetary Fund (IMF) is sufficiently differentiated among LICs. The lending framework appears to not fully meet LICs' needs for contingent financing, especially the most advanced of them. To be prepared for future crises, IDA should investigate other funding models to reduce its dependence on annual donor budget processes and increase the volume of its shock windows. With regard to middle-income countries (MICs), the paper confirms that the IFIs' quick response helped to contain a larger systemic crisis. However, for various reasons, the IMF's facilities were not used much, while the International Bank for Reconstruction and Development (IBRD) greatly expanded its policy lending, thus using up a large part of its lending headroom. This calls for a revision of the IBRD's crisis instruments for MICs.
Keywords: 330; Regionale + globale + transnationale Governance; Entwicklungsfinanzierung und öffentliche Finanzen